The Role of Profitability Intervening Variables in Stock Return Model - Hakim, Luqman; Wanialisa, Mery; Puspitaningtyas, Ayu (Jurnal Multidisiplin Madani, 2024)
This research aims to explore the impact of the Loan to Deposit Ratio (LDR) and Interest Rates (IR) on the profitability indicators, specifically Return on Assets (ROA) and Stock Return (SR). The motivation for this investigation arises from observed differences in various research findings and real-world events, prompting a reassessment by researchers. The study adopts a quantitative descriptive approach, employing panel data multiple regression analysis with 20 cross-sectional samples spanning a 6-year time series. The research formula is crafted to optimize Stock Return by including Return on Assets as an intervening variable, focusing particularly on companies within the banking sector listed on the Indonesia Stock Exchange. Two distinct research models are formulated and integrated into a unified model, subjected to rigorous model selection tests such as Chow Test, Hausman Test, and Lagrange Multiplier Test. The study's results suggest that LDR can only indirectly influence SR through the mediating role of ROA. Furthermore, IR has a direct impact on SR without the mediation of ROA. These findings are expected to offer valuable guidance for banking practitioners in Indonesia and market participants, aiding them in maximizing Stock Returns